Crack Extension Analysis of Atmospheric Stress Corrosion Based on Peridynamics - Can Tan; Songrong Qian; Jian Zhang (Applied Sciences, 2022)
Based on peridynamics, an atmospheric stress corrosion model was proposed. In this model, the role of hydrogen and stress in anodic-dissolution-dominated stress corrosion cracking was considered, and atmospheric corrosion was characterized by the change in liquid film thickness on the metal surface in the atmospheric environment. The near-field kinetic anodic dissolution model and the atmospheric corrosion model were coupled by varying the liquid film thickness. The thickness of the liquid film depended on factors such as the temperature, relative humidity, and hygroscopic salts. We validated the model using stress corrosion behavior from the literature for 304 stainless steel in a simulated atmospheric environment. The results of the model captured the crack expansion process. The obtained crack expansion direction and branching behavior agreed well with the experimental results in the literature.